Dagbok fra en Sydhavstur 1906 - Sørlle, Petter; Kolltveit, Bård (Norsk sjøfartsmuseum. Årbok, 2005)
Keywords: Sørishavet; dagbøker; hvalfangere; hvalfangstindustri; hvalindustri; hvalkokeri; polareksspedisjoner

The race for the South Pole: Robert Scott and Roald Amundsen (1911-12) - Fleming, Fergus (Off the map : tales of endurance and exploration, 2004)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; oppdagelsesreiser; polareksspedisjoner

Blant pelssel og pingvinar. Ei julereise til Sør-Georgia og Antarktis - Kolltveit, Bård (Norsk sjøfartsmuseum. Årbok, 2003)
Keywords: Antarktis; cruiseturisme; dagbøker; polareksspedisjoner; reisebeskrivelser; reiseskildringer

Women and couples in isolated extreme environments: applications for long-duration missions - Leon, Gloria R.; Sandal, Gro Mjeldheim (Acta Astronaut, 2003)
Expedition teams provide a number of analogs relevant to crew selection for long-duration space missions. Three groups were studied that varied in team composition. Group 1 was a two woman international dyad that traversed the Antarctic continent in 97 days. Similarities in problem solving approach, respect for each other's opinions, and a collaborative process of decision making were evident. Group 2 was composed of four women, all from different countries, engaged in a six week trek across Greenland. The most important factors in overcoming interpersonal difficulties and contributing to the successful completion of the expedition were mutual respect and motivation to maintain positive and supportive relationships. Group 3 consisted of three married couples from different countries icelocked on a boat in the High Arctic for a 9 month period. The emotional support of and ability to confide in their partner were extremely important in alleviating interpersonal tensions, and contributed to the generally effective functioning of the group. Women add an element of emotional support and help to other team members that is not as evident in all-male groups. Selection of couples with strong bonds to each other is another paradigm for crew selection for extended missions.
Keywords: Antarktis; polareksspedisjoner; polarforskere; polarområdene; psykologi

Antarctica - Sale, Richard (To the ends of the Earth : the history of Polar exploration, 2002)
This text provides an insight into the early history of the Polar regions, and tells the stories of Man's first exploration of the Arctic and Antarctic, and subsequent expeditions. The history of individual Polar expeditions has been told many times, but usually only as personal accounts of individual adventures. This misses the overall context of polar exploration - why the British depended on ponies, or plant-eating animals (on the only continent where plants don't grow), why Franklin's men perished when the local Eskimos were eking out an existence around them (and reporting Franklin's demise), and why the Scandinavians were always better than anybody else. The first map of Antarctica was produced in 1556 - the Vikings visited the Arctic 1,000 years before. In 2001, the US Base at the South Pole is manned 365 days a year. The book tells the whole story of how the two last wildernesses, at either end of the world, were discovered, conquered and tamed.
Keywords: Antarktis; Belgica ekspedisjon; Carsten Egeberg Borchgrevink; Nordmenn; Norge; Roald Amundsen; Southern Cross; Sydpolsekspedisjonen; ekspedisjonen; historie; hvalfangst; oppdagelsesreiser; pelagisk; polareksspedisjoner

Noen problemer i den moderne hvalfangsts historie - Tønnessen, Johan Nicolay (Vestfold-minne, 1964)
Keywords: Carl Anton Larsen; Henrik Johan Bull; Svend Foyn; Sørishavet; historie; hvalfangstindustri; hvalfangstselskaper; hvalindustri; næring; pelagisk; polareksspedisjoner; økonomi

Amundsen the Opportunist. The Dash for the Pole - Judd, Alfred (The conquest of the poles : and modern adventures in the world of ice, 1923)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; oppdagelsesreiser; polareksspedisjoner

Steam whalers; First Antarctic night - Mill, Hugh Robert (The siege of the south pole : the story of antarctic exploration, 1905)
Keywords: Antarctic (skip); Antarktis; Carl Anton Larsen; Carsten Borchgrevink; Henrik Johan Bull; Kapp Adare; oppdagelsesreiser; overvintring; polareksspedisjoner; vitenskap